PS 14-65 THE EFFECTS OF BAROREFLEX ACTIVATION THERAPY ON BLOOD PRESSURE AND SYMPATHETIC FUNCTION IN PATIENTS WITH REFRACTORY HYPERTENSION – THE RATIONALE AND DESIGN OF THE NORDIC BAT STUDY. (September 2016) - Kjeldsen, Sverre E; Elmula, Fadl Elmula M. Fadl; Gordin, Daniel; Andersson, Bert; Gottsäter, Anders; Kahan, Thomas; Christensen, Kent Lodberg; Olsen, Michael Hecht; Tikkanen, Ilkka
Abstract : Objective: Baroreflex activation therapy (BAT) modulates the autonomic nervous system to restore sympathovagal balance. The aim of this study is to explore the long-term effects of BAT on blood pressure (BP) in patients with refractory (true resistant) hypertension (RH). Design and Method: This academic (independent of industry support) randomized, double-blind, 1:1 parallel-design clinical trial will include 100 patients with RH from 5 hypertension centers in the Nordic countries. A Barostim Neo® System will be implanted and after 1 month of stabilization patients will be randomized to either BAT (BAT on) for 16 months or continuous pharmacotherapy (BAT off) for 8 months followed by the BAT (BAT on) for 8 months. Eligible patients will be 18–70 years and have a daytime systolic ambulatory blood pressure (ABMP) of 145 mmHg or more, and/or a daytime diastolic ABMP of 95 mmHg or more, after witnessed intake of antihypertensive treatment (including at least 3 antihypertensive drug classes, preferably including a diuretic), with no changes in medication for a minimum of 4 weeks prior to enrolment. Patients with secondary causes of hypertension, severe renal insufficiency, untreated sleep apnea, type 1 diabetes, alcohol abuse, severe valvular diseases will be excluded. Results: The primary end point is to test whether BAT reduces 24-hour systolic ABMP at 8 months of follow-up compared to pharmacotherapy. Secondary and tertiary end points are the effects of BAT on home and office blood pressure, measures of autonomic function, arterial and cardiac structure and function during follow-up, and extended long-term follow-up. Two patients have been included in the study so far. An interim analysis will be done after 50 patients. Preliminary results are thus awaited during the year 2018. Conclusions: This initiative will increase the understanding of the mechanisms and role of BAT in the treatment of RH. (ClinicalTrials.gov identifierNCT02572024 ).